Analisis Penggunaan Media Edukasi E-Booklet Terhadap Peningkatan Pengetahuan Dan Sikap Mahasiswa Tentang Kebutuhan Gizi: Analysis of Using E-Booklet Educational Media to Improve Students' Knowledge and Attitudes Towards Nutritional Needs - Sandy, Yatty Destani; Rukmana, Erni; Damanik, Kanaya Yori; Pratiwi, Caca; Putri, Kalasta Ayunda (Amerta Nutrition, 2026)
Background: University students, as late adolescents transitioning into young adulthood, require adequate nutritional intake to achieve optimal nutritional status. Nutritional knowledge and attitudes play an essential role in shaping healthy eating behaviors; however, previous studies indicate that the majority of students (>70%) still have a limited understanding of daily nutritional requirements. The use of digital-based educational media, such as e-booklets, is considered a promising strategy due to its accessibility, flexibility, and interactive features. Objectives: To analyze the effect of e-booklet based nutrition education on students’ knowledge and attitudes regarding nutritional requirements. Methods: A quasi experimental study with a one-group pre test and post test design was conducted among 60 active undergraduate students from the Fashion Design Study Program at Universitas Negeri Medan, selected using stratified random sampling. Data were collected using pre test and post test questionnaires and analyzed using the paired sample t test and the Wilcoxon test. Results: The results showed an increase in mean knowledge scores by 20.58 points and attitude scores by 7.91 points after the intervention, with a statistically significant effect (p-value = 0.000). These findings indicate that e-booklet based nutrition education significantly improved students’ knowledge and attitudes toward nutritional requirements. Conclusions: E-booklet educational media is effective in enhancing students’ knowledge and attitudes toward nutrition. This approach can be recommended as an innovative alternative in nutrition education and as a practical health promotion strategy for adolescents and young adults. E-booklets can be integrated into school curricula as a more engaging and interactive method of nutrition instruction.